Laboratory Markers of Chronic and Acute Stress: Diagnostic Value and Clinical Implications (Part 2: Neuroendocrine, Immunological and Metabolic Biomarkers of Chronic Stress in the Context of Its Influence on Cardiovascular System) - Shkvarok-Lisovenko, Anastasiia; Bushman, Yevheniia (The Ukrainian Scientific Medical Youth Journal, 2025)
Chronic stress (CS) is a powerful factor that silently, but persistently undermines human health by dysregulating the hypothalamic-pituitary-adrenal (HPA) axis and autonomic nervous system (ANS). Its manifestation goes far beyond emotional experiences, shaping profound physiological changes that affect the endocrine, immune and metabolic systems. Modern biomarkers allow us both to visualize these changes and measure their intensity, making them quantifiable and clinically relevant. A comprehensive literature review was conducted, encompassing 76 English-language sources identified through PubMed, Scopus, Web of Science and Google Scholar. The analysis focused on the interplay between the hypothalamic–pituitary-adrenal (HPA) axis, the autonomic nervous system (ANS), and stress-related conditions (CS). The search strategy targeted peer-reviewed publications from 2020 to 2025 using the following keywords: “cardiovascular system“, “acute stress“, “chronic stress“, “cortisol“, “epinephrine“, “norepinephrine“, “dehydroepiandrosterone“, “dopamine“, “aldosterone“, “tumor necrosis factor alpha“, “interleukin-1“, “interleukin-6“, “C-reactive protein“, “cholesterol“, “albumin“ and “glycosylated hemoglobin“. Inclusion criteria comprised original research articles, systematic and narrative reviews, meta-analyses and clinical guidelines, while non-peer-reviewed sources and non-English publications were generally excluded. The article summarizes key laboratory markers of stress, from classical hormones (cortisol, epinephrine, ACTH) to immune and metabolic indicators (cytokines, C-reactive protein, oxidative stress markers), with particular attention to hair cortisol as an innovative tool for long-term stress assessment. Stress-related biomarkers provide an integrated view of CS pathophysiology, demonstrating how neuroendocrine, immune and metabolic dysregulation drives hypertension, cardiovascular events, insulin resistance, systemic inflammation and neuropsychiatric disturbances. Early detection and management of CS are essential to prevent cumulative damage that can progress to obesity, metabolic syndrome, atherosclerosis, neurodegeneration and increased morbidity and mortality.